PIDANA MATI TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DI INDONESIA - Abimaniu, I Putu Indra Yoga; Mertha, I Ketut; Wirasila, A.A.Ngr (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
Today narcotics in Indonesia has been spread, it can be seen at this time inIndonesia not only as a place of narcotics but it has become a place for manufacture ofnarcotics. To prevent this crime, the government has been released a lot of an Act toregulate narcotics and now has been used that is Act 35 in 2009. In this Act there is apunishment that causes polemic that is Death penalty, this polemics said that the deathpenalty is contrary to the Constitution of 1945 and there are say that the death penaltystill need to be implemented to give a deterrent effect on drug abuser. From the problemhence the authors make minithesis with the title "Dead Penalty For Narcotics Abuser inIndonesia".
Keywords: Criminal, Criminal Goal, Death Penalty, Narcotics.